Pencabutan Hak Memilih pada Penyelesaian Kasus Waris bagi Umat Islam dalam UU No. 3 Tahun 2006 Perspektif Sadd al-Zari'ah - Muh. Hidayat; Hendra Wijaya; Abdul Munawir (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the background of the emergence of Law No. 3 of 2006 and the settlement of Islamic inheritance cases before and after the emergence of Law No. 3 of 2006, as well as the application of the concept of sadd al-zari'ah on the revocation of the right to vote on the settlement of Muslim inheritance cases in Law No. 3 of 2006. The type of research used is descriptive qualitative research, which focuses on manuscript and text studies using a normative juridical approach method and is supported by historical and conceptual approach methods. From the results of this study it was found that the revocation of the right to choose in the settlement of inheritance cases for Muslims in Law No. 3 of 2006 is in accordance with the concept of sadd al-zari'ah. The revocation prevents dualism in Islamic inheritance law and the emergence of various mafsadat.